ANALISIS STRATEGI PEMASARAN USAHA PENGOLAHAN KOPI LEGATO - Redjeki, Sri (Prosiding Seminar Nasional: Manajemen, Akuntansi, dan Perbankan; Vol 1 No 1 (2018): Prosiding Seminar Nasional dan Call for Papers Manajemen, Akuntansi, dan Perbankan 2018, 2018)
This research is aimed to formulate recommendation of marketing strategy for LEGATO coffee processing business. The research is qualitative by using primary data source and secondary data. Data collection techniques used were interviews, observation, and documentation. SWOT Matrix Analysis and Internal-External Matrix Analysis is used to obtain marketing strategy that is suitable with company condition. Based on SWOT Matrix Analysis, there are four alternative marketing strategies that can be chosen by the company. Each is: a combination of Strength-Opportunity, Strength-Threat, Weakness-Opportunity, Weakness-Threat. Furthermore, the results of the Internal-External Matrix analysis show the total IFAS and EFAS scores of firms are 2,478 and 2,620 which means the company has average internal and external capabilities. Recommended strategy is an implement of market penetration and increasing promotion through participation at various events  either locally, regionally, and nationally.